2018
DOI: 10.1080/2000656x.2018.1498792
|View full text |Cite
|
Sign up to set email alerts
|

The lateral arm flap for reconstruction of tissue defects due to olecranon bursitis

Abstract: Wound healing problems following acute and chronic olecranon bursitis can result in problematic tissue defects around the elbow. These defects often require a regional flap or a free flap for durable tissue coverage. The aim of this study was to assess clinical outcome the lateral arm flap (LAF) used to cover tissue defects caused by chronic olecranon bursitis. Between 2011 and 2015, 13 patients with soft tissue defects of the elbow resulting from chronic bursitis olecrani were treated in an interdisciplinary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated the benefits of various local flaps and regional pedicled flaps for elbow reconstruction (di Summa et al, 2020; Elhassan et al, 2011; Heidekrueger et al, 2018; Nakao et al, 2018; Tung et al, 1997; Türegün et al, 2005; Zampeli et al, 2019). However, high rates of reoperation and unsuccessful definitive coverage following total elbow arthroplasty have been reported, resulting in subsequent free flap reconstruction (Adkinson & Chung, 2014; Patel & Higgins, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the benefits of various local flaps and regional pedicled flaps for elbow reconstruction (di Summa et al, 2020; Elhassan et al, 2011; Heidekrueger et al, 2018; Nakao et al, 2018; Tung et al, 1997; Türegün et al, 2005; Zampeli et al, 2019). However, high rates of reoperation and unsuccessful definitive coverage following total elbow arthroplasty have been reported, resulting in subsequent free flap reconstruction (Adkinson & Chung, 2014; Patel & Higgins, 2013).…”
Section: Introductionmentioning
confidence: 99%